Interactions between different biological forms of aquatic macrophytes in a eutrophic tropical reservoir in Northeastern Brazil - Lycarião, Thainá Alves; Dantas, Ênio Wocyli (Revista de Biología Tropical, 2017)
The aquatic plants and biological processes have different interactions and their knowledge may contribute to the understanding of environmental dynamics in wetlands. The aim of this study was to report the type of interactions that different biological forms of macrophytes stand in the eutrophic tropical reservoir of Penha reservoir, Northeastern Brazil. Data collection was captured every two months from October 2009 to October 2010, considering the hydrological cycle in one-year period. For this, twelve perpendicular transects (separated by 10 m) at the reservoir’s water edge were defined; each transect had two plots of 625 cm² (25 x 25 cm, separated by one meter) from which samples were obtained. Plants were collected and transported in identified plastic bags for subsequent quantification of the dry weight biomass; additionally, pressed samples were made in the field for identification purposes. The relative interaction index (RII) was used to identify the existence of positive and/or negative interactions between the biomass of the biological forms of aquatic plants. Student’s t-tests were used to analyze variations in the abiotic data and biomass over time, and to determine differences between the dry and rainy seasons. Pearson and Spearman correlation coefficients were calculated to determine correlations between the biological forms and the biomass of the macrophytes, as well as environmental variables and RII. In the dry season, the environment was mainly composed of floating macrophytes (1 013.98 g/m²), with mats of submerged macrophytes (98.18 g/m²) that demonstrated a range of positive (RII= 1.0) to negative (RII= -0.2) interactions. The biomass of emergent macrophytes increased throughout the dry season (4.87 to 106.91 g/m²) due to the nurse plant effect that served as a substratum (RII= 1.0). During the rainy season the biomass of submerged macrophytes was reduced by 97 % due to direct and indirect relationships (RII= -1.0) to other macrophytes. Rainfall and emergent plants contributed to a reduction in the biomass of floating macrophytes (19.16 g/m²). The emergence of a third group of plants (emergent) lead floating plants to occupy other areas and excluded submerged plants. Overall, the interactions among plants within ecosystems were not definite due to stand composition and seasonality.